2015
DOI: 10.1186/s13229-015-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+ reverses functional deficits in a de novo dopamine transporter variant associated with autism spectrum disorder

Abstract: Our laboratory recently characterized a novel autism spectrum disorder (ASD)-associated de novo missense mutation in the human dopamine transporter (hDAT) gene SLC6A3 (hDAT T356M). This hDAT variant exhibits dysfunctional forward and reverse transport properties that may contribute to DA dysfunction in ASD. Here, we report that Zn2+ reverses, at least in part, the functional deficits of ASD-associated hDAT variant T356M. These data suggest that the molecular mechanism targeted by Zn2+ to restore partial functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Our assessment of structural changes in T356M showed, in agreement with recent findings (53), that Zn 2+ partly rescues uptake function of T356M. A similar Zn…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our assessment of structural changes in T356M showed, in agreement with recent findings (53), that Zn 2+ partly rescues uptake function of T356M. A similar Zn…”
Section: Discussionsupporting
confidence: 92%
“…Remarkably, Zn 2+ produced even larger MTSET-dependent inhibition of dopamine uptake for both T356M (~80%), and D421N (~75%) even though these variants display opposite conformational preferences in the absence of Zn 2+ . The molecular mechanisms underlying Zn 2+ -dependent rescue of T356M function are highly interesting, and could provide important insight into molecular mechanisms of allosteric activators of DAT, which has been suggested to hold therapeutic potential (47,53 . Trace recordings of voltage clamped oocytes showed that dopamine indeed elicits an aberrant outward current through T356M (Fig.…”
Section: +mentioning
confidence: 99%
“…Maternal inflammation has been previously shown to cause offspring deficits in latent and prepulse inhibition, along with decreased social and exploratory behavior (Smith et al, 2007), which are associated with dopamine dysfunction and mental health disorders such as schizophrenia and ASD. The increased inflammation that accompanies maternal HFD consumption likely impacts the dopaminergic system of offspring, causing increased risk of psychopathology as changes in the dopaminergic system are associated with disorders such as ASD(Bowton et al, 2014; Hamilton et al, 2015; Staal, 2014), ADHD (Hasler et al, 2015; Pan et al, 2015; Tong et al, 2015), schizophrenia (Howes et al, 2015; Slifstein et al, 2015; Sumiyoshi et al, 2014), anxiety (Agius et al, 2014; Lee et al, 2015), and depression (Clausius et al, 2009; Dunlop and Nemeroff, 2007). …”
Section: Mechanisms By Which Maternal High-fat Diet Consumption mentioning
confidence: 99%
“…DAT has been implicated in ADHD by the efficacy of stimulant medications, which treat the disorder and block the DAT (Yanli Zhang-James, 2015) along with suggestive findings from genetic association studies (Faraone et al, 1999; Faraone et al, 2014). Some reports of DAT associated with ASD and ADHD have focused on mutations, such as the V559 and the T356M variants, that cause the transporter to anomalously efflux dopamine into the synaptic cleft (Hamilton et al, 2015; Mazei-Robison et al, 2008). In addition to anomalous dopamine efflux during basal level neurotransmission, the V559 coding variant was found in two autism probands and was found to have trafficking disruptions (Bowton et al, 2014).…”
Section: : Reviewmentioning
confidence: 99%